Islamic Business Ethics in Qs. Al-Jumu'ah Verses 9-10 From The Perspective of Quraish Shihab - Fitriyah, Wardatul (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan Jawa Timur, 2024)
Humans were created and placed on Earth not only to worship but also to serve as leaders (khalifah). However, fulfilling this role effectively is impossible if their basic needs are unmet. The fulfillment of these needs is a fundamental obligation that must be prioritized. To meet these needs, humans must strive and work, and one of the ways to do so is through business. Ethics is essential in shaping and building attitudes in all aspects, including business ethics. In Islam, business is not aimed at short-term goals or purely for individual gain but also considers long-term objectives, including one's relationship with Allah SWT. In the Qur'an, work is always linked to faith, indicating a close relationship between faith and activities, akin to the roots of a plant and its fruit. Therefore, when it is time to worship, it must be prioritized, as seen in the command for men to perform Friday prayers before continuing their work. The concept of business ethics in Islam has a different emphasis compared to conventional business ethics. These differences arise due to the distinct foundational principles and thought processes behind each approach. Islamic business ethics are based on the Qur'an and Hadith, the consensus and reasoning of scholars (ijma' and qiyas), and the business experiences within the Muslim community. Islamic Business Ethics can be understood through several concepts, including the Concept of Godliness, the Concept of Ownership as a Trust, the Concept of Good and Right according to Islam, the Concept of Responsibility, the Concept of Honesty, and the Concept of Justice. These concepts form the foundation of an Islamic business code of ethics, which serves as the legal basis for resolving disputes and enhancing brotherhood (Ukhuwah).